Continuous manufacturing of nanofiber yarn with the assistance of suction wind and rotating collection via needleless melt electrospinning. Issue 20 (27th January 2017) - Ma, Xiaolu; Zhang, Liyan; Tan, Jing; Qin, Yongxin; Chen, Hongbo; He, Wanlin; Yang, Weimin; Li, Haoyi
ABSTRACT: Nanofiber yarn was continuously manufactured by a needleless melt‐electrospinning method. The suction wind speed was the most important factor influencing the final fiber diameter and determining whether the fibers could be gathered into a well‐aligned strand. The twisting process of the yarn was performed by the adjustment of ratio of the speed of the collecting roller to the speed of the rotating disk. The results show that the higher the assisting suction wind speed was, the smaller the fiber diameter was. The smallest average fiber diameter of 440 nm was obtained at a suction wind speed of 30 m/s. Furthermore, the smaller the ratio of the speed of the collecting roller to the speed of the rotating disk was, the larger the twisting angle of the prepared yarn was. The largest twisting angle obtained in this study was 43 ° at the greatest ratio of the speed of the collecting roller to the speed of the rotating disk. The X‐ray diffraction results show that the alignment degree of the nanofiber twisting and the crystallinity increased with increasing twisting angle. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44820. Abstract :